A systematic review of the implementation of Industry 4.0 in human resources - Shreesha, R. (BOHR International Journal of Operations Management Research and Practices, 2023)
The advancement of both society and the economy may be traced back to the industrial sector. Businesses and academic institutions alike have shown considerable enthusiasm for the Industry 4.0 initiative. Although “Industry 4.0” as a concept has been explored in academic circles for some time, it is only recently that the term has become popular in both academic and industrial settings. Academic studies, on the other hand, aim to better the industrial sector by clarifying the meaning of the concept and developing relevant systems, business models, and methodologies. Businesses need a thorough understanding of the features and substance of Industry 4.0 in order to make the transition from machine-dominated to digital production. These data will be useful when they formulate a plan. Along this route, there have been many discussions and plans put forth. The rapid progress of industrial science is linked to this ailment. This paper conducts a literature review to investigate the relationship between Industry 4.0 and the development of industrial engineering science, the challenges that this field faces, and the impact that the industrial revolution had on human resources, all of which contributed to the emergence of Industry 4.0. To improve productivity, efficiency, and unemployment, the concept merges digital technologies, the Internet, and conventional industries. Moreover, some of the ramifications concern the detrimental effects of Industry 4.0 on human resources. The fundamental objective is to furnish labor forces with tools by expanding employment and spawning new avenues for business ownership across several industries and institutional configurations